DISCOURSE OF WEST-UKRAINIAN COMEDY OF THE 20-th – 30 th OF THE XX CENTURY (BASED ON GRIGOR LUZHNYTSKY’S PLAYS) - Rodchyn, Z. Ya. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The object of the article is a comedy as well as its place in Grygor Luzhnytski’s dramatic works. Symbolic attributes of the analyzed genre, poetics peculiarities of Western Ukrainian dramatist’s writings are in the centre of the research.